A comparative study on the jet loop reactor and continuos stirred tank reactor in the selective hydrogenation of palm olein (I.V.64) - Tea, Swee Sin (2005)
Jet Loop Reactor (JLR) was developed to improve the overall performance of hydrogenation processes. Nevertheless, the application of JLR in the palm oil and oleochemical industries in Malaysia is still very much sparse. A substantial amount of investment and the lack of study conducted in Malaysia on the application of JLR have retarded the retrofitment and/or replacement of the conventional CSTR with this technology. In the wake of this, a comparative study was conducted to investigate the performance of JLR in the selective hydrogenation of palm olein with an IV of 64 in comparison to the hydrogenation in the conventional CSTR system. A pilot scale JLR with a capacity of 250 liter was used in the study. The circulation of the sample in the loop was achieved via a single speed pump. The experimental result was compared with result from the CSTR experiment. A down-scaled laboratory CSTR apparatus was used in the study for this purpose. A software package, developed via Microsoft Excel 2000 and Visual Basic Application (VBA) softwares, was used to simulate the behavior of the hydrogenation process in both, JLR and CSTR, under similar capacity. The outcome of the study showed that with the limitation of single speed pump, the JLR could not matched the superiority of CSTR in the selective hydrogenation process for it required slow reaction to produce high trans fatty acids hydrogenated product. On the positive note, the developed software package is a useful tool which allows an easy method to study the behavior of the hydrogenation process of JLR and CSTR. The prediction of the CSTR process was acceptable, but the prediction of JLR process was less accurate, revealing a maximum of 30% error. It can be concluded that the present analytical method used in the simulation of JLR required improvement on the modeling of the process, or to opt for the numerical solution, to produce a much better prediction. A retrofit method was also suggested in the study, for the possibility of fitting in the JLR facility in the existing CSTR system with minimal modification, for the system to have dual function of slow and fast reactions.